Social Reproduction in Schools of Excellence from the Perspective of Pierre Bourdieu - Hilman Haris Wicaksono (Didaktika: Jurnal Kependidikan, 2024)
This study aims to prove the reproduction of social inequalities that occur in excellent schools. According to Bourdieu, schools have a significant role in maintaining social inequality because it is a place where the habits and cultural capital of individuals are formed, which then affects their educational path and life chances (Bourdieu, 2020); (Carter, 2003) (McKinney, 2013) (Mills, 2021). The problem of education gap in schools is a complex problem that is influenced by various factors. In previous studies there were differences in capital backgrounds in families, inequality in the distribution of educational resources, privatization of private schools and gender differences were some of the factors that influenced the education gap. This research uses a qualitative approach. Data collection techniques and methods using snowball, this method involves the use of initial informants to recommend and connect researchers with other potential informants according to research objectives. The object of research is a final year student (grade 9) who attends a school with a superior level label in Magelang City, Central Java. The findings of this study show that students who experience inequality in education due to differences in capital owned in the same educational environment. (Chiu, 2015; Grant, 2017; Munir & Kanwal, 2020; Ogawa, 2022)(Creswell & Creswell, 2017) Mohd The sun, 2022).